HUBUNGAN ANTARA CRITICAL THINKING ABILITY DENGAN COMMUNICATION ABILITY MATEMATIS SISWA MTSN 1 MUSI BANYUASIN TAHUN PELAJARAN 2019/2020 - UPIK MUKRAMIYAH (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2022)
This study aims to determine the relationship between Critical Thinking Ability and Mathematical Communication Ability of class IX students of MTs Negeri 1 Musi Banyuasin in mathematics learning in the odd semester of the 2019/2020 school year. The research method used in this research is descriptive method. The population of this study was all class IX of MTs Negeri 1 Musi Banyuasin in the odd semester of mathematics learning in the 2019/2020 school year, while the sample used was class IX A and IX B, totaling 56 students. The sampling technique used is the purposive sampling technique. The data collection technique used is the test. The data analysis technique used is the Spearman correlation test. Based on the results of the data obtained, the average Critical Thinking Ability of students in the initial and final tests was 71.65 and 75.00, which were in the good category. Meanwhile, the average mathematical communication ability of students in the initial and final tests was 72.32 and 76.79, which were also in the good category. Data Critical Thinking Ability and Communication Ability of students mathematically in the final test increased to the initial test by 3.35 points and 4.47 points, respectively. Furthermore, the data were analyzed to determine the normality of the students' mathematical Critical Thinking Ability and Communication Ability data. The Spearman Correlation Test obtained a significance value of 0.00 < 0.01 so that Ho was rejected and it was concluded that there was a significant relationship between the Critical Thinking Ability and the Mathematical Communication Ability of the students of MTs Negeri 1 Musi Banyuasin in learning mathematics. ABSTRAKPenelitian ini bertujuan untukmengetahui hubungan antara Critical Thinking Ability dengan Communication Ability matematis siswa kelas IX MTs Negeri 1 Musi Banyuasin pada pembelajaran matematika semester ganjil tahun pelajaran 2019/2020. Metode Penelitian yang digunakan dalam penelitian ini adalah metode deskriptif. Populasi penelitian ini adalah seluruh kelas IX MTs Negeri 1 Musi Banyuasin pada pembelajaran matematika semester ganjil tahun pelajaran 2019/2020, sedangkan sampel yang digunakan adalah kelas IX A dan IX B yang berjumlah 56 siswa. Teknik Pengambilan sampel yang digunakan adalah Teknik Purposive Sampling. Teknik Pengumpulan data yang digunakan adalah Tes. Teknik Analisis Data yang digunakan adalah uji korelasi Spearman. Berdasarkan hasil data yang diperoleh, rata-rata Critical Thinking Ability siswa pada tes awal dan tes akhir masing-masing sebesar 71,65 dan 75,00 yang berada pada kategori baik. Sementara, rata-rata Communication Ability matematis siswa pada tes awal dan akhir masing sebesar 72,32 dan 76,79 yang juga berada pada kategori baik. Data Critical Thinking Ability dan Communication Ability matematis siswa pada tes akhir mengalami peningkatan terhadap tes awal masing-masing sebesar 3,35 poin dan 4,47 poin. Lebih lanjut, data dianalisis untuk mengetahui kenormalan data Critical Thinking Ability dan Communication Ability matematis siswa. Uji Korelasi Spearman diperoleh nilai signifikasi 0,00 < 0,01 sehingga Ho ditolak dan diperoleh kesimpulan bahwa terdapat hubungan signifikan antara Critical Thinking Ability dan Communication Ability matematis siswa MTs Negeri 1 Musi Banyuasin pada pembelajaran matematika.